Association of circulating long non‐coding RNA HULC expression with disease risk, inflammatory cytokines, biochemical index levels, severity‐assessed scores, and mortality of sepsis. Issue 3 (13th December 2020) - Wang, Haiyan; Feng, Qiang; Wu, Yiping; Feng, Lingxiang; Yuan, Haiyan; Hou, Liyan; Wei, Peixuan; Wang, Chao; Wang, Jingmei
Abstract: Background: The present study aimed to explore the correlation of long non‐coding RNA highly up‐regulating in liver cancer (lncRNA HULC) with disease risk, inflammatory cytokines, biochemical indexes, disease severity, infective features, and 28‐day mortality of sepsis. Methods: Totally 174 sepsis patients and 100 controls were enrolled. Peripheral blood samples were collected from sepsis patients after diagnosis and from controls at enrollment, respectively, and further for separation of peripheral blood mononuclear cell (PBMC) and serum samples. PBMC samples were for lncRNA HULC detection, and serum samples were for inflammatory cytokine detection. Results: LncRNA HULC expression was increased in sepsis patients compared with controls. Moreover, lncRNA HULC was positively associated with TNF‐α, IL‐6, IL‐17, intercellular adhesion molecule 1, vascular cell adhesion molecule 1, serum creatinine, white blood cell, and C‐reactive protein in sepsis patients, but not in controls. Furthermore, in sepsis patients, lncRNA HULC expression was positively correlated with acute physiology and chronic health evaluation II score and sequential organ failure assessment score, but not correlated with primary infection sites or primary infection organisms; meanwhile, lncRNA HULC expression was increased in deaths compared with survivors; subsequent receiver operating characteristic curve indicated that lncRNA HULC presented good value in predicting increased 28‐day mortality (AUC: 0.785, 95% CI: 0.713–0.857), and its independent predictive value for mortality was also verified by multivariate analysis. Conclusion: LncRNA HULC is correlated with higher disease risk, severity, and inflammation and serves as an independent factor for predicting increased mortality, suggesting its potential in promoting accuracy of prognostic prediction for sepsis management. Abstract : Totally 174 sepsis patients and 100 controls were enrolled and their peripheral blood samples were collected and separated for lncRNA HULC and inflammatory cytokine detection. Results indicated that lncRNA HULC expression was increased in sepsis patients compared with controls; LncRNA HULC was positively associated with higher inflammation level in sepsis patients, but not in controls; In sepsis patients, lncRNA HULC expression was positively correlated with increased disease severity, and serves as an independent factor for predicting increased mortality.